School Work Environment and Teachers' Job Satisfaction in Private Senior Secondary Schools, Kwara State, Nigeria - Adeseko Sunday Olaifa; Folake Sherifat Halim; Ebunlomo Oreoluwa Olaifa; Muritala Adaramaja Sheu; Godwin Oluwaseyi Are (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
This study examined the relationship between the school work environment and teachers' job satisfaction in private senior secondary schools in Kwara State, Nigeria. The main purpose was to identify the available school work environments and assess their influence on teachers' job satisfaction, with specific objectives exploring dimensions such as physical environment, administrative support, workload management, collegial relationships, and workplace policies. A descriptive survey research design of the correlational type was adopted. The population comprised all teachers and principals in private senior secondary schools across Kwara State, Nigeria. A multi-stage sampling technique was employed, involving purposive selection of local government areas, and proportional selection of 319 teachers and principals. Data were collected using a self-designed questionnaire titled the School Work Environment and Teachers' Job Satisfaction Questionnaire (SWETJSQ), which was validated by experts and tested for reliability in a pilot study, yielding a Cronbach's Alpha coefficient of 0.73. Descriptive statistics (mean, standard deviation) answered research questions, while Pearson Product-Moment Correlation (PPMC) tested hypotheses at the 0.05 significance level. Findings indicated that school work environments were adequately available, teacher job satisfaction was high, and significant positive relationships existed between all environmental dimensions and job satisfaction components (salary, health, welfare, and promotion). Recommendations include improving infrastructure, administrative support, workload balance, collegial collaboration, and fair policies to enhance teacher retention and performance.